Toward Social and Emotional Learning for Justice-Involved Youth: A Conceptual Framework (Journal of Applied Juvenile Justice Services, 2024)
Social and emotional learning (SEL) has been used in many K-12 schools across the United States to improve academic and nonacademic outcomes. Extensive research affirms SEL’s benefits for students in educational settings. However, there is a research gap in adaptations of SEL for alternate settings. This article conceptualizes a SEL framework for justice-involved youth on community supervision to support rehabilitation efforts in the juvenile justice system (JJS). Integrating SEL into JJS may reduce recidivism and help justice-involved youth develop the skills to reintegrate into society successfully.